2008
DOI: 10.1002/cncr.23771
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of comorbidity in salivary gland carcinoma

Abstract: BACKGROUND.Patients with head and neck cancer are prone to develop significant comorbidity mainly because of the high incidence of tobacco and alcohol abuse, both of which are etiologic and prognostic factors. However, to the authors' knowledge little is known regarding the prognostic relevance of comorbidity in patients with salivary gland cancer.METHODS.A retrospective cohort of 666 patients with salivary gland cancer was identified within the Dutch Head and Neck Oncology Cooperative Group database. For mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 42 publications
4
38
2
Order By: Relevance
“…In the present study, several clinical and pathologic characteristics were shown to be independent prognostic factors for OS and CSS in patients with MSGC, including age, sex, tumor site, tumor grade, surgery performed, radiation therapy, and TNM classifications, which is consistent with previous reports [5, 6, 8, 11, 2730]. Apart from these, comorbidity and postoperative complications, which were not included in the present study, have been proven to be accurate prognostic factors [11, 30].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, several clinical and pathologic characteristics were shown to be independent prognostic factors for OS and CSS in patients with MSGC, including age, sex, tumor site, tumor grade, surgery performed, radiation therapy, and TNM classifications, which is consistent with previous reports [5, 6, 8, 11, 2730]. Apart from these, comorbidity and postoperative complications, which were not included in the present study, have been proven to be accurate prognostic factors [11, 30].…”
Section: Discussionsupporting
confidence: 93%
“…19 Factors that statistically shorten survival included high T stage, highgrade malignancy, and FN paralysis on diagnosis. 1 According to Terhaard et al, 20 the most important independent factors negatively affecting survival rate include young age, high T and N stages, skin infiltration, and male gender. However, Takahama et al 21 did not observe any relation between these variables and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multivariate analysis for overall survival in salivary gland malignancies showed that patient comorbidity was a strong independent prognostic variable [14]. Results of the multivariate analysis using the Cox regression model, including patient comorbidities as categorical variables, are summarized in Table 4.…”
Section: Multivariate Analysismentioning
confidence: 99%